Emerging trends in India-Pakistan trade - Nisha Taneja; Samridhi Bimal; Varsha Sivaram (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Significant measures were undertaken by India and Pakistan to liberalize trade in 2012. In particular, Pakistan's policy to permit all items to be imported from India except for a few items was expected to bring about a quantum increase in India's exports. Similarly, India's efforts to address Non-Tariff Barriers (NTBs) were expected to lead to an increase in Pakistan's exports to India. This study focuses on understanding whether there has been substantial increase in trade since 2012 and whether there has been a change in commodity composition of traded items. It also examines whether new items have entered India's export basket and assesses whether these items indicate a shift from informal to formal trade. The study identifies key trade policy reform measures undertaken by the two countries which are likely to impact India-Pakistan trade. These measures include regulatory duties imposed by Pakistan and Goods and Service Tax (GST) adopted by India. The key finding of the study is that there has been a limited impact of trade liberalization on the volume of trade between the two countries. The shift from positive list to negative list has not resulted in any major increase in new exports. The share of new commodities exports in total exports has showed a rise of only 9 percentage points between 2012-13 and 2016-17. However, the trade basket has witnessed a diversification in terms of number of new items traded. The study finds that there is evidence of items shifting from informal to formal channels. The study also finds that the imposition of regulatory duties and compliance of standards has not affected India's exports to Pakistan. The study concludes by making policy recommendations that could enhance and facilitate bilateral trade between India and Pakistan.
Keywords: F10; F13; F50; F53; 330; India-Pakistan; bilateral trade; trade normalization; informal trade